Class and Culture in Recent Anglo-American Religious Historiography: A Review Essay - Tucker, Bruce (Labour / Le Travail, 1980)
The article reviews and comments on "A Shopkeeper's Millennium: Society and Revivals in Rochester, New York, 1815-1837," by Paul E. Johnson, "Crusade in the City: Revivalism in Nineteenth Century Philadelphia," by Marion L. Bell, "Transatlantic Revivalism: Popular Evangelicalism in Britain and America, 1790-1865," by Richard Carwardine, "Religion and Respectability: Sunday Schools and Working Class Culture, 1780-1850," by Thomas W. Laqueur, "Revivals, Awakenings and Reform: An Essay on Religion and Social Change in America, 1607-1977," by William G. McLoughlin, "Gospel Hymns and Social Religion: The Rhetoric of Nineteenth-Century Revivalism," by Sandra S. Sizer, "Rockdale: The Growth of an American Village in the Early Industrial Revolution," by Anthony F.C. Wallace, "Vision of the Disinherited: the Making of American Pentecostalism," by Robert M. Anderson, and "The Second Coming: Popular Millenarianism, 1780-1850," by J.F.C. Harrison.